Association Between Acidosis Soon After Reperfusion and Contrast‐Induced Nephropathy in Patients With a First‐Time ST‐Segment Elevation Myocardial Infarction. Issue 8 (23rd August 2017) - Gohbara, Masaomi; Hayakawa, Azusa; Akazawa, Yusuke; Furihata, Shuta; Kondo, Ai; Fukushima, Yusuke; Tomari, Sakie; Endo, Tsutomu; Kimura, Kazuo; Tamura, Kouichi
Abstract : Background: Contrast‐induced nephropathy (CIN) is associated with poor outcomes in patients with acute myocardial infarction. However, the predictors of CIN have yet to be fully elucidated. Methods and Results: The study included 273 consecutive patients with a first‐time ST‐segment elevation myocardial infarction who underwent reperfusion within 12 hours of symptom onset. The exclusion criteria were hemodialysis, mechanical ventilation, or previous coronary artery bypass grafting. All patients underwent arterial blood gas analysis soon after reperfusion. CIN was defined as an increase of 0.5 mg/dL in serum creatinine or a 25% increase from baseline between 48 and 72 hours after contrast medium exposure. Acidosis was defined as an arterial blood pH <7.35. CIN was observed in 35 patients (12.8%). Multivariable logistic regression analysis with forward stepwise algorithm revealed a significant association between CIN and the following: reperfusion time, the prevalence of hypertension, peak creatine kinase‐MB, high‐sensitivity C‐reactive protein on admission, and the incidence of acidosis ( P <0.05). Multivariable logistic regression analysis revealed that the incidence of acidosis was associated with CIN when adjusted for age, male sex, body mass index, amount of contrast medium used, estimated glomerular filtration rate on admission, glucose level on admission, high‐sensitivity C‐reactive protein on admission, and left ventricular ejection fraction ( P <0.05). Moreover, the incidence of acidosis was associated with CIN when adjusted for the Mehran CIN risk score (odds ratio: 2.229, P =0.049). Conclusions: The incidence of acidosis soon after reperfusion was associated with CIN in patients with a first‐time ST‐segment elevation myocardial infarction.